Model Pemetaan Destinasi Wisata Syariah di Jawa Timur Berbasis Teknologi Blockchain: Pendekatan Smart Halal Tourism Ecosystem - Suradi, Amran; Musfiqoh, Siti (Journal of Industrial and Syariah Economics, 2026)
The development of halal tourism in East Java has shown significant potential, reflected in the growth of religious destinations, Islamic cultural attractions, and a rapidly expanding halal industry. However, the current halal tourism ecosystem faces challenges related to fragmented destination data, limited integration of halal certification, and low transparency of information for visitors. This study aims to formulate a blockchain-based mapping model for halal tourism destinations, designed as a foundation for a Smart Halal Tourism Ecosystem. A mixed-methods approach was applied through ecosystem needs assessment, digital readiness surveys of industry actors, and expert interviews with halal regulators and destination managers. The findings indicate that blockchain can provide a transparent and tamper-proof halal verification system while enhancing the credibility of destination information. The proposed model consists of four core components: the Halal Data Verification Layer, Smart Mapping Layer, User Interaction Layer, and Governance & Regulator Layer. This study contributes theoretically by integrating smart tourism frameworks with halal blockchain architecture and offers practical policy recommendations to strengthen halal tourism governance in East Java.